The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1524-4725.1988.tb01157.x
|View full text |Cite
|
Sign up to set email alerts
|

Management Considerations for Cutaneous Neurophilic Tumors

Abstract: The proper management of patients with neurophilic skin cancers is often quite difficult. When present, neurophilic invasion significantly worsens the prognosis. Important considerations for managing patients with cutaneous neurophilic tumors and illustrative cases are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 23 publications
0
51
0
Order By: Relevance
“…Skip areas have been postulated as an explanation for false-negative surgical margins by several authors. 13,[43][44][45] Although most false-negative margins may be explained by less than perfect processing of Mohs surgical specimens, 46 Wallerian degeneration as postulated in this case could cause the loss of small peripheral nerve axons, resulting in noncontiguous perineural invasion.…”
Section: Discussionmentioning
confidence: 80%
“…Skip areas have been postulated as an explanation for false-negative surgical margins by several authors. 13,[43][44][45] Although most false-negative margins may be explained by less than perfect processing of Mohs surgical specimens, 46 Wallerian degeneration as postulated in this case could cause the loss of small peripheral nerve axons, resulting in noncontiguous perineural invasion.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, when tumors invade nerves, Mohs surgery has its limitation in identifying perineural invasion conclusively due to possible false “skip areas” or the so-called “discontinuous perineural extension.” Nevertheless, Mohs surgery, by examining 100% of the surgical margin utilizing horizontal sections, still has increased sensitivity as compared to routine histological processing, in which equivalent to 0.01% of the specimen surface area is evaluated [30, 31]. As perineural inflammation and “skip areas” due to tissue processing may indicate proximal perineural invasion, some authors advocate the removal of an additional Mohs layer after tumor-free margins are obtained [32, 33]. We would like to share our experience in managing cutaneous malignancies with perineural invasion in general.…”
Section: Discussionmentioning
confidence: 99%
“…7 Cutaneous tumors with perineural invasion are generally associated with increased aggressiveness, extensive soft-tissue spread, and an increased incidence of recurrence, and increased morbidity and mortality. [8][9][10][11][12][13][14][15] This underscores the need for a consistent diagnostic criteria of perineural involvement (PNI). Dunn et al 16 defined PNI as the presence of cytologically malignant cells observed in the perineural space of nerves.…”
Section: Introductionmentioning
confidence: 99%